TEKNIK FORMULASI RANSUM UNTUK PENINGKATAN PRODUKSI ITIK PADA UKM JAYA MAKMUR DI DESA KARAWANG SARI LAMPUNG SELATAN - Sukaryana, Yana; Priabudiman, Yadi; Patria, Cintia Agustin; Pertiwi, Vindo Rossy; Usman, Nurul Azizah; Kafi, Suraya; Susanti (Politeknik Negeri Lampung, 2022)
Efforts that can be taken in community welfare and development programs are the fulfillment of thequality and quantity of animal protein. An alternative to meet the needs of meat/animal protein is fromducks. However, in reality the maintenance of ducks often experiences problems with the length ofharvest and the quality of meat that contains a lot of cholesterol, and the mortality of livestock is veryhigh so that the use of banana peels is expected to increase the intestinal microflora and immunity ofducks and can reduce cholesterol levels of duck meat, so that productivity increases. The purpose ofthe community service program engaged in agriculture-food using banana peels is to pioneer theformation of SMEs engaged in the production of low-cholesterol ducks, develop a pilot business forlow-cholesterol duck products using banana peels, and apply various innovations and findings relatedto the use of banana peels. so that it can be more easily applied by society and industry. The result ofthe extension and mentoring activities was an increase in understanding and application of rationformulations by partner duck farmers. In addition, increasing the production and welfare of partnerduck farmers in Kerawan Sari Village, South Lampung Regency.